Political Documentary Cinema in the Southern Cone - Traverso, Antonio; Crowder-Taraborrelli, Tomas (Sage, 2013)
Documentary cinema in Argentina, Chile, and Uruguay has shown comparable degrees of vibrancy and sophistication since the 1950s, as well as a shared desire to be a key witness to unfolding political events and a protagonist in national and regional processes of social justice. Southern Cone political documentary cinema today constitutes a substantial body of work that possesses great potential as a source for understanding social change histories in Latin America. This article historically and conceptually maps the political documentary of Argentina, Chile, and Uruguay since the 1950s and the scholarly study in English and Spanish that has focused upon the former. The article also serves as a critical introduction to the edited collection Political Documentary Film and Video in the Southern Cone (1950s-2000s), which appeared as a special issue of the journal Latin American Perspectives (vol 40, number 1, January 2013) and looks closely at the strategies utilized by Argentine, Chilean, and Uruguayan political filmmakers to document and participate in social change events, as well as to imagine and reflect upon the past and the future of these three South American nations.